Diseño de las instalaciones eléctricas del parque mirador del municipio de Aguazul departamento de Casanare - Celis Márquez, Laurentino (Universidad Antonio Nariño, 2023)
Design of the electrical installations of the mirador park of the municipality of Aguazul, department of Casanare